2005
DOI: 10.1677/jme.1.01711
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, heterologous expression and pharmacological characterization of a kappa opioid receptor from the brain of the rough-skinned newt, Taricha granulosa

Abstract: A full-length cDNA that encodes a kappa ( ) opioid receptor has been isolated from the brain of a urodele amphibian, the rough-skinned newt Taricha granulosa. The deduced protein contains 385 amino acids and possesses features commonly attributed to G protein-coupled receptors, such as seven putative transmembrane domains. The newt receptor has 75% sequence identity to opioid receptors cloned from mammals, and 66% sequence identity to the opioid receptor reported for the zebrafish, with the greatest divergence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 68 publications
(91 reference statements)
0
9
0
Order By: Relevance
“…This notion was supported by significant evidence: both j-opioid agonists and CORT suppress clasping behavior (Deviche and Moore, 1987), CORT suppresses clasping by acting at a membrane receptor mCR (Orchinik et al, 1991) and rapidly up-regulating endogenous cannabinoid signaling (Coddington et al, 2007), mCR has j-like properties (Bradford et al, 2005), and specific j-opioid agonists bind and compete with CORT for the mCR with high affinity (Evans et al, 2000). Consistent with past research, this study found that the j-opioid agonist U50488 significantly suppressed clasping in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This notion was supported by significant evidence: both j-opioid agonists and CORT suppress clasping behavior (Deviche and Moore, 1987), CORT suppresses clasping by acting at a membrane receptor mCR (Orchinik et al, 1991) and rapidly up-regulating endogenous cannabinoid signaling (Coddington et al, 2007), mCR has j-like properties (Bradford et al, 2005), and specific j-opioid agonists bind and compete with CORT for the mCR with high affinity (Evans et al, 2000). Consistent with past research, this study found that the j-opioid agonist U50488 significantly suppressed clasping in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 91%
“…U50488 binds to both the mCR and it's own native jOR in in vitro preparations of Taricha brains; binding to the mCR with the same affinity as CORT (K i = 250 nM; (Evans et al, 2000)), and binding its own receptor (jOR) with a higher affinity (K i = 3.4 nM; (Bradford et al, 2005). Furthermore, the mCR has a single CORT binding site that has very high specificity and affinity for the CORT and j-opiate ligands, and very low affinity for mineralocorticoids or classical intracellular glucocorticoid receptor antagonists (Orchinik et al, 1991;Evans et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The genes arose by duplications in the common ancestor of tetrapods and bony fishes (13). Opioid receptor sequences have been reported for a few nonmammalian tetrapods (14)(15)(16)(17)(18)) and a few teleost fishes (19)(20)(21)(22)(23)(24), and a partial sequence has been reported for a hagfish (19). Functional studies in amphibians and bony fishes have shown that the opioid system is involved in nociception also in these species (25,26).…”
mentioning
confidence: 99%
“…The first full-length clone sequenced from a nonmammalian species was ccMOR from the brain of the white suckerfish, Catostomus commersoni (Darlison et al, 1997). Other nonmammalian species with full-length opioid receptors cloned are the zebrafish, Danio rerio, by Rodriguez and colleagues (Alvarez et al, 2006;Barrallo, González-Sarmiento, Alvar, & Rodriguez, 2000;Barrallo, González-Sarmiento, Porteros, Gracia-Isídoro, & Rodríguez, 1998;Porteros, Garcia-Isodoro, Barrallo, González-Sarmiento, & Rodriguez, 1999) and the rough-skinned newt, Taricha granulosa, in the laboratory of Moore (Bradford, Walthers, Searcy, & Moore, 2005;Bradford, Walthers, Stanley, Baugh, & Moore, 2006;. Using the same sets of primers that Evans group used in the first phylogenetic study of opioid receptors (Li et al, 1996b), our group was able to clone all four opioid receptor types expressed in R. pipiens brain tissue: rpMOR, rpDOR, rpKOR, and rpORL (Stevens, Brasel, & Mohan, 2007).…”
Section: The Vertebrate Opioid Receptor Sequence Databasementioning
confidence: 99%